The Applicability of Twenty-First Century Skills in English as a Foreign Language (EFL) Classrooms: Potentials and Challenges - Alasmari, Nasser (International Journal of Psychosocial Rehabilitation, 2020)
Learning, nowadays, is no longer restricted to the comprehensive acquisition and full grasp of facts and truths. In a century that brings along large advances in information and communication technologies (ICT) in addition to the “unprecedented challenges” at all level; social, economic and environmental, learners from all over the world are required to acquire certain skills and competencies in order to keep up with these advances and challenges and guarantee their positions as active partakers in the labour market in the future. With this in mind, light has been shed on the role of education, especially at the tertiary level, to aid learners achieve such goals. This study was carried out in a newly founded establishment namely the University of Jeddah and had as objective to investigate the extent to which the 21st century skills, which are classified into three sets, are applied and acquired as well as the potential challenges that may hamper the applicability of such skills. Results showed that the participants in this study are frequently and professionally using the ICT set of skills while the third set namely life and career is given less importance from the part of the same subjects. Peer-dominance and proficiency discrepancy are among the challenges that Saudi learners face to acquire the 21st century skills. The findings also imply that Saudi pedagogists and educators need to agree on the skills to be considered the most critical, to pay them particular focus and thus come up with well- defined frameworks that organize the interrelationship between learning and skills so as to create and adopt the most appropriate teaching methods that would help the Saudi learners acquire and develop these key skills.